PENGARUH KEPEMILIKAN MANAJEMEN, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sianturi, Mari Ani; Yando, Agus Deffri (LPPM Universitas Putera Batam, 2021)
The motive of this take a look at to plot ownwership, company length and profitability ofcompany cost. This studies become performed in all items region production corporationsindexed at the 2015-2019 di Bursa Efek Indonesia. The pattern used on this take a look atbecome nine corporations sectors that produced patron items at the Bursa Efek Indonesia2015-2019. The sampling technic makes use of purposive sampling. This take a look atmakes use of IBM SPSS V.21 statistical Software. With regression and the distinctionamong the simultan massive have an impact on among control possession, organisationlength and profitability and company cost are wanted through different elements now nolonger associated on this take a look at. While primarily based totally on partial studiesthrough different elements now no longer mentioned on this take a look at. While primarilybased totally at the partial take a look at the outcomes display there's a high quality andnow no longer contradicted among control possession and organisation length of theorganisation cost, whilst profitability and company cost undoubtedly and notably have aneffect on the cost of the organisation.